The effect of indoor environmental quality on occupant's perception of performance in old student dormitories of University of Malaya / Chu Kok Wei - Chu, Kok Wei (2015)
It is known that the people are spending most of their time indoors and therefore the occupants' performance and well-being are greatly affected by the various aspect of indoor environmental quality. Academic achievement loss occurred in the institutions is the result of stress which causes low achievement of academic excellence. Dissatisfaction and excess workload may result to some extent of stress.